Comparative efficacy of chloroquine and pyrimethamine-sulfadoxine versus artemether and pyrimethamine-sulfadoxine in the treatment of uncomplicated falciparum malaria in children - Femmy Tambajong; Tonny H Rampengan (Paediatrica Indonesiana, 2004)
Background Large amount of data show that chloroquine andpyrimethamine-sulfadoxine (PS) as standard drugs for falciparummalaria cause resistance; for that reason new drugs or combina-tion drugs are urgently needed. Artemether is one of the newdrugs. It has been studied extensively in China and SoutheastAsia during the past 10 years. The effectiveness of this drug inclearing parasites has been thoroughly documented.Objective The objective of this study was to investigate theefficacy of the combination of chloroquine and PS compared toartemether and PS in the treatment of uncomplicated falciparummalaria.Methods We did a single-blind randomized study on 60 childrenwith uncomplicated falciparum malaria. Thirty children weretreated with chloroquine (10 mg/kg for 2 days, then 5 mg/kg inthe 3 rd day) and PS (pyrimethamine 1-1.5 mg/kg single dose onthe 1 st day) and the other 30 children were treated with artemether(4 mg/kg/day for 3 days) and PS. All patients were admitted tohospital for at least 7 days.Results Fever clearance time was significantly shorter in the groupthat received artemether and PS compared to that in the chloro-quine-and-PS group (42 hours vs. 75 hours 50 minutes, p<0.0001).Parasite clearance time was significantly different between thegroup that received artemether and PS and the chloroquine-and-PS group (2.5 days vs. 3.1 days, p=0.04). The cure rate in thechloroquine-and-PS group was 28/30 and that of the artemether-and-PS group was 30/30. Nausea and vomiting were found in 1patient treated with chloroquine and PS.Conclusion The combined treatment of artemether and PS waswell tolerated. No adverse reactions attributable to the treatmentwere noted